Deactivation pathways of thiophene and oligothiophenes: internal conversion versus intersystem crossing. Issue 11 (25th February 2016) - Kölle, Patrick; Schnappinger, Thomas; de Vivie-Riedle, Regina
Abstract : Quantum chemical calculations reveal that excited thiophene decays via a low lying conical intersection seam. In oligothiophenes barriers inhibit this passage while deactivation pathways via intersystem crossing channels open. Abstract : Oligothiophenes and polythiophenes are building blocks of organic-based energy conversion materials. Therefore the lifetime of the excited states plays a central role. As a first step to understand the factors influencing the performance, we investigated the deactivation processes from the first excited state S1 of thiophene and small oligothiophenes containing up to four rings using quantum chemical calculations. For thiophene a low-lying S1 /S0 conical intersection seam is easily accessible and drives the fast internal conversion. In oligothiophenes barriers inhibit this passage while deactivation pathways via intersystem crossing channels open. The first one is responsible for the high triplet quantum yields and takes place shortly after the Franck–Condon region. The second one occurs in the vicinity of a local S1 minimum. The calculated spin–orbit coupling strength together with the singlet–triplet energy gaps can explain the decreasing triplet and increasing fluorescence quantum yields for growing chain length. From the triplets the ground state is reachable by inter-ring torsions and T1 /S0 intersections. The present results allow a deeper understanding of the deactivation pathways of thiophene and small oligothiophenes and are of potential interest for the photophysics of longer oligothiophenes and polythiophenes used in optical devices.